Peran Patient-Centered Communication dan Komunikasi Terapeutik Terhadap Kepuasan Pasien di Rumah Sakit: Scoping Review - Dessy Marlinda Primasari; Septo Pawelas Arso; Apoina Kartini (Jurnal Ners, 2026)
Abstract Communication in healthcare services is an important indicator in determining the quality of hospital services, particularly in improving patient satisfaction. This study aims to analyze the role of communication, both patient-centered communication (PCC) and therapeutic communication, on patient satisfaction in hospitals through a scoping review. The scoping review was conducted based on the PRISMA-ScR guidelines using the PCC framework, which includes population (patients receiving hospital services), concept (healthcare communication such as PCC, therapeutic communication, and interpersonal communication), and context (hospital services). Article searches were conducted through PubMed, Scopus, Cochrane Library, and Google Scholar databases using the keywords (“patient-centered communication” OR “therapeutic communication”) AND (“patient satisfaction”) AND (“hospital”). A total of 18 articles met the inclusion criteria and reported that effective communication has a significant relationship with increased patient satisfaction across various hospital service units, including inpatient, outpatient, and emergency departments. The most influential aspects of communication include empathy, clarity of information, patient involvement, and the ability of healthcare providers to build interpersonal relationships and trust. In addition, other factors such as response time, service quality, and cleanliness also contribute to patient satisfaction, although their influence is not as strong as communication. These findings indicate that improving the communication skills of healthcare providers is an important strategy to enhance service quality and patient satisfaction in hospitals. Keywords: patient-centered communication, therapeutic communication, patient satisfaction, hospital services, scoping review.